Social inclusion of adult people with intellectual disabilities in Croatia - Ostojić Baus, Jasna; Gašpar Čičak, Andrea; Jakovčev, Mirjana (Specijalna edukacija i rehabilitacija, 2024)
Introduction. Contemporary social policies aimed at individuals with disabilities are grounded in the social model of disability. As a result, the primary objective of social policy towards individuals with disabilities globally, within the EU, and also in Croatia, is the pursuit of social inclusion following the initiation of deinstitutionalization. Objectives. This research aimed to examine the social inclusion of adults with intellectual disabilities in Croatia. The primary objective involved identifying dimensions or factors within the social inclusion Questionnaire. Additionally, the study sought to explore potential correlations between the age and gender of adults with intellectual disabilities and their level of social inclusion. Method. The study comprised 145 adults with intellectual disabilities, residing with their families in various cities across the Republic of Croatia. A questionnaire specifically tailored to measure the social inclusion of people with intellectual disabilities was developed. Results. The final version of the Questionnaire singled out 4 factors within the construct of social inclusion: Social environment and physical health; Inclusion and human rights; Mental health and relationships with family and friends; and Economic well-being. The findings revealed that there were no statistically significant associations between the social inclusion of individuals with intellectual disabilities and either their age or gender. Conclusion. It is important to develop better measurement instruments for social inclusion and to conduct research on a larger sample of individuals not involved in non-governmental programs. The impact of age and gender should also be examined qualitatively to identify specific characteristics. Additionally, according to the descriptive data, there is a need for improved educational programs and employment opportunities for people with intellectual disabilities.